2018
DOI: 10.1111/1468-0009.12349
|View full text |Cite
|
Sign up to set email alerts
|

How Equity‐Oriented Health Care Affects Health: Key Mechanisms and Implications for Primary Health Care Practice and Policy

Abstract: Policy Points A consensus regarding the need to orient health systems to address inequities is emerging, with much of this discussion targeting population health interventions and indicators. We know less about applying these approaches to primary health care.This study empirically demonstrates that providing more equity‐oriented health care (EOHC) in primary health care, including trauma‐ and violence‐informed, culturally safe, and contextually tailored care, predicts improved health outcomes across time for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
208
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(222 citation statements)
references
References 80 publications
2
208
0
4
Order By: Relevance
“…Items from the larger EQUIP study reflect the key dimensions of equity‐oriented health care as identified by the EQUIP research team and were modified for use in the NP clinic to explore women's experiences of EOHC, including 30 Likert‐based items as outlined in Table (Browne et al, , ; Ford‐Gilboe et al, ). As outlined above, the larger set of items were developed by the EQUIP team based on a comprehensive literature review of a variety of different scales and analyses related to equity‐based care (Browne et al, , ; Ford‐Gilboe et al, ; ). The larger set of items were developed from item response theory using patient cohort data ( n = 567) for the larger EQUIP study (Browne et al, , ; Ford‐Gilboe et al, ; ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Items from the larger EQUIP study reflect the key dimensions of equity‐oriented health care as identified by the EQUIP research team and were modified for use in the NP clinic to explore women's experiences of EOHC, including 30 Likert‐based items as outlined in Table (Browne et al, , ; Ford‐Gilboe et al, ). As outlined above, the larger set of items were developed by the EQUIP team based on a comprehensive literature review of a variety of different scales and analyses related to equity‐based care (Browne et al, , ; Ford‐Gilboe et al, ; ). The larger set of items were developed from item response theory using patient cohort data ( n = 567) for the larger EQUIP study (Browne et al, , ; Ford‐Gilboe et al, ; ).…”
Section: Methodsmentioning
confidence: 99%
“…As outlined above, the larger set of items were developed by the EQUIP team based on a comprehensive literature review of a variety of different scales and analyses related to equity‐based care (Browne et al, , ; Ford‐Gilboe et al, ; ). The larger set of items were developed from item response theory using patient cohort data ( n = 567) for the larger EQUIP study (Browne et al, , ; Ford‐Gilboe et al, ; ). The development of those items is discussed in detail in a prior publication and is summarised below (Ford‐Gilboe et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations